Lung Cancer in Peru - Ruiz, Rossana (2020)
Peru is a South American nation with a growing and aging population of 31 million people with a life expectancy at birth of 76.7 years. The country is divided into 25 regions, 79% of the population is urban, and Lima, the capital, concentrates more than a third of the population.1 Although Peru is an upper-middle-income country, health expenditure represents only 5.1% of the gross domestic product, which is lower than the average of Latin America and the Caribbean (LATAM) (8.56%).2 Out-of-pocket health expenditure is 30.9%.3 Peru has a comprehensive National Cancer Plan and two population-based cancer registries in Lima and Arequipa.